Prevelence and economic inference of small ruminant foetal wastage at the Kumasi Abattoir Ltd (Kaase) - Mohammed, Alhassan; Anane, Kwame (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2022)
Postmortem survey of small ruminant pregnancy wastage was conducted at Kumasi Abattoir Ltd, Kaase. Abattoir visits and investigations were conducted on 16 randomly selected abattoir working days. All mature ewes and does slaughtered on selected abattoir working days (mean = 71.69 animals/day) were included in the study, giving a total of 1,147 animals (301 ewes and 846 does). The reproductive tracts of study animals were collected at slaughter line and the uterus were grossly inspected for pregnancy. Thereafter, uterine body and horns were longitudinally incised to check the lumen for a visible fetus. The type of pregnancy (single or twin) was recorded and crown-rump length (CRL) of the largest fetus was demarcated on a piece of string and measured on a standard measuring tape. The length of gestation was estimated using the formula; Developmental Age (Days) = 2.1(Y+17), where Y = the CRL in “cm”. A survey was conducted within the premises of the Kumasi abattoir to estimate the average prices of matured small ruminants to calculate the prevailing market value of small ruminants. The potential economic impact of small ruminant abattoir fetal wastage was estimated by calculating the gross economic value and net economic value forgone due to loss of potential offspring. Kumasi Abattoir Annual Off-take was estimated to be 26,095 small ruminants where 73.8% were does and 26.2% were ewes. Pregnant does slaughtered had 37.2% of them carrying single foetus and 12.5% carrying twin foetus whereas pregnant ewes slaughtered had 28.9% carrying single foetus and 9.3% carried twin foetus. Total pregnancy wastage recorded had 3.7% early pregnancy and 96.3% mid-pregnancy with no late pregnancy recorded. Economic losses due to pregnancy wastage was estimated to be from GHS 2,755,140.80 to 3,534,791.80. The greater amounts of foetal waste encountered, places a substantial risk not only to the livestock production sector, but also to the economy of the nation.